Factor XII: New life for an old protein - Schmaier, Alvin H.; LaRusch, Gretchen (Thrombosis and Haemostasis, 2010)
Ratnoff and his coworkers recognised that factor XII (XII) stimulates cell growth and activates mitogen-activated protein kinase. We determined the receptor(s) for this function and the consequence of this signalling pathway. Investigations show that the urokinase plasminogen activator receptor serves as the XII binding site on cultured umbilical vein endothelial cells. When XII binds, it stimulates ERK1/2 and Akt S473 phosphorylation. These events are distinct because when cell mTORC2 is absent, XII phosphorylates ERK1/2 but not Akt S473. Zymogen XII is an equal stimulator of signalling as XIIa or inhibitor-treated XIIa. Peptides from uPAR domain 2 block XII binding and ERK1/2 and Akt phosphorylation. Furthermore, antibodies to the integrins β1 and α5 block XII signalling. Likewise, inhibitors to the EGFR block XII-induced phosphorylation events. XII stimulates cell growth and proliferation. XII induces angiogenesis ex vivo in normal aortic sprouts and in vivo in matrigel plugs in normal mice, but not in aorta from uPAR knockout mice or matrigel plugs placed into uPAR-deleted mice. Skin biopsies constitutively or in a wound nine days after injury show reduced CD31 antigen expression in specimens from XII knockout mice compared to wild-type mice. These studies indicate that XII stimulates angiogenesis, a physiologic function independent of contact activation.
Keywords: Angiogenesis and inhibitors, contact phase, urokinase / receptor, factor XII, integrins